Granular fermentation enables high rate caproic acid production from solid-free thin stillage. Issue 6 (25th February 2019) - Carvajal-Arroyo, José M.; Candry, Pieter; Andersen, Stephen J.; Props, Ruben; Seviour, Thomas; Ganigué, Ramon; Rabaey, Korneel
Abstract : Disc shaped microbial aggregates enriched in Ruminococcaceae and lactic acid bacteria produced caproic acid from solid-free thin stillage. Abstract : Microbial chain elongation has been investigated as a process to upgrade diluted ethanol to more valuable medium chain carboxylic acids. However, its application in the valorization of (agro)industrial wastes or sidestreams has been hampered by low volumetric production rates. Microbial granulation, widely applied in wastewater treatment, has been rarely explored in a context of bioproduction. Here we show how fermentative granulation can be applied to the valorization of solid-free thin stillage, through a high-rate chain elongation process for the production of MCCA without the addition of exogenous electron donating intermediates. Using a fermentative expanded granular sludge bed reactor, caproic acid was produced at sustained rates of 12.3 g C6 L −1 d −1 (625 mmol C L −1 d −1 or 27.2 g C6-COD L −1 d −1 ) at pH 5.5, and concentrations of up to 6.8 g C6 L −1 . During a stable period (days 181–217) the 27.2% of the influent fermentable COD was converted to caproic acid. During the same period caproic acid accounted for 44.4% of the produced carboxylic acid-C, with butyric and acetic acids generated as main side-products, but a maximum specificity of 58.4% had been previously observed. Lactic acid served as the electron donating intermediate, to the extent that no net ethanol was consumed. The granules developed into disc-shaped aggregates and were enriched in chain elongating Ruminococaceae, while the planktonic biomass was dominated by lactic acid bacteria. The characterization of the extracellular polymeric substances (EPS) showed that polymers of high molecular weight (>10 6 Da) were more abundant in the granules than in the planktonic biomass.